TINDAK PIDANA PENCUCIAN UANG DAN PENEGAKAN TINDAK PIDANA KORUPSI - Halim, Pathorang (Al-Qisth Law Review, 2017)
Money laundering, has been known in the world since the 1930s, with activities, from organized crime, from the proceeds of crime dark, for further bleached by the company with various business services. In Indonesia, money laundering, always get attention, in various writings, through research, seminars, but not fully implemented by law enforcement. Results PPATK, not followed by police investigators, although there is a strong desire, that the Commission, has started using money loundering laws, especially those associated with corruption.